2014
DOI: 10.1155/2014/920491
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association of the PolymorphismsIL-17A(−197G/A) andIL-17F(+7488A/G) with Multibacillary Leprosy in Mexican Patients

Abstract: Background. Leprosy is a chronic infectious disease caused by the intracellular acid-fast bacilli Mycobacterium leprae; it has been determined that genetic factors of the host play an important role in the disease susceptibility. Thus, in this case-control study, we evaluated the possible association between the IL-17A G-197A (rs227593) and IL-17F A7488G (His161Arg, rs763780) gene SNPs and susceptibility to leprosy disease in Mexican population. Methods. Seventy-five leprosy patients and sixty-nine control sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Consistent with our data, Escamilla‐Tilch et al. () found no association between the IL17A and IL17F polymorphisms and MB leprosy in Mexican patients. However, in a north Indian cohort, the IL17F T7488C was associated with susceptibility to leprosy (Chaitanya et al., ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our data, Escamilla‐Tilch et al. () found no association between the IL17A and IL17F polymorphisms and MB leprosy in Mexican patients. However, in a north Indian cohort, the IL17F T7488C was associated with susceptibility to leprosy (Chaitanya et al., ).…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, it has been reported that the IL-8 production can be stimulated by IL-17A and IL-17F (Lavocat, Maggi, Annunziato, & Miossec, 2016;Okamoto Yoshida et al, 2010), which are produced by Th17 cells and have been associated with leprosy and formation of a mycobacterial infection-induced granuloma in the lung (Escamilla-Tilch et al, 2014 744) genes contain polymorphisms associated with the secretion of IL-17 (Espinoza et al, 2011); these were also included.…”
Section: Introductionmentioning
confidence: 99%
“…They found no association between IL-17A (rs2275913A/G) gene SNPs and leprosy. 20 Therefore, the present study confirmed the evidence of a lack of relationship between IL-17A (rs2275913A/G) gene polymorphism and leprosy susceptibility.…”
Section: Discussionsupporting
confidence: 88%
“…They found that genotype frequencies had non-significant differences in the overall leprosy patients and controls. 19 Also, Escamilla-Tilch et al 20 investigated 75 Mexican Mestizo leprosy patients versus 69 controls. Sixty-two patients were classified as LL, 2 as TL, 2 as BL, and 9 as dimorphic.…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis and to limit any confounding bias (latitude, etc. ), we focused on the countries whose IL‐6 gene polymorphisms at rs1800796 and rs1800795 loci, IL‐6R gene polymorphism at rs2228145 locus, IL‐10 gene polymorphism at rs1800896 and rs1800871 loci, IL‐17A gene polymorphism at rs2275913 and IL‐17F gene polymorphism at rs763780 loci were defined and the allele frequencies were reported in 54 studies 10–63 . We searched the literature for the interleukin gene polymorphisms determined in the populations of China, Japan, India, Spain, Mexico, Sweden, Turkey, Brazil, Russia, Poland, Italy, South Africa, Netherlands, Greece, Germany, UK, Iran, Finland, Czechia, Tunisia, Norway, Egypt, Croatia.…”
Section: Methodsmentioning
confidence: 99%